Dasatinib‐therapy induced sustained remission in a child with refractory TCF7‐SPI1 T‐cell acute lymphoblastic leukemia. Issue 8 (20th April 2022) - He, Yingyi; Zhang, Jingliao; Zhang, Yingchi; Hu, Zhengbin; Wang, Pengfei; Gan, Wenting; Xie, Shao; Qian, Maoxiang; Pui, Ching‐Hon; Jiang, Hua; Zhu, Xiaofan; Zhang, Hui; et al.
Abstract: The prognosis of patients with T‐cell acute lymphoblastic leukemia (T‐ALL) has been largely lacked behind than that of patients with B‐cell ALL, especially in refractory or relapsed cases. Here, we describe a 4.7‐year‐old male child with TCF ‐ SPI1 ‐postitve T‐ALL who developed refractoriness disease after a seven drugs‐conventional therapy. Several studies have suggested the therapeutic potential of dasatinib in refractory T‐ALL. Actually, dasatinib‐included therapy dramatically reduces the leukemic burden and re‐induces this patient into complete remission without systemic adverse events. Although this is a single exceptional case, the translational potential evidence of dasatinib in specific T‐ALL subtype should not be under‐estimated.